THEORETICAL ASPECTS OF INFORMATION PROVISION OF RESTAURANT ENTERPRISE MANAGEMENT PROCESSES - Nebaba, N. O.; Kucher, M. M.; Yazina, V. A.; Saihak, Ye. L.; Golovko, N. O. (Systems and Technologies, 2023)
The article is devoted to consideration of modern information support of restaurant enterprise management processes. It is established that the information support system organizes the collection, processing, storage and transmission of information to support various processes in the restaurant business. The information system consists of hardware, software and organizational components that cooperate to achieve effective management and is a key tool for effective management of a restaurant enterprise, which contributes to achieving competitive advantages and ensures improvement of service quality. The essence and characteristics of the system of information support of restaurant enterprise management processes have been studied. The constituent elements of information support in the management of a restaurant enterprise are considered. The classification of information technologies according to categories is provided. The advantages and features of information support for restaurant enterprise management processes are given. It has been established that information technologies are an integral part of the restaurant business, because they contribute to the automation and optimization of restaurant management processes, improve communication with customers, provide fast and convenient service, increase the efficiency of the kitchen and allow analyzing data to make better management decisions. Recommendations on the effective use of information support in restaurants are provided. It was analyzed that for the effective introduction of new technologies it is important to ensure proper training of the staff and support from the management. Adequate infrastructure and information security should also be provided to ensure data reliability and confidentiality. It has been studied that the introduction of modern information technologies and improvement of information support can significantly increase the efficiency and competitiveness of a restaurant enterprise. With proper planning, development and implementation of new technologies, the enterprise will be able to provide high quality customer service, increase its attractiveness in the market and improve its financial indicators.